Effect of galangal essential oils on rumen microbial population and biodiversity on in vitro rumen fermentation - Dewi Ratih Ayu Daning; Budi Prasetyo Widyobroto; Lies Mira Yusiati; Chusnul Hanim (Indonesian Journal of Biotechnology, 2022)
The study aimed to evaluate the effect of administering galangal essential oil (EO) on the abundance of rumen bacteria using the 16s rRNA method. The treatments included a control (no EO addition), galangal EO (30, 60, 120 µL), and cineole (5 µL). The treatments were assessed using a 48‐hour in vitro batch culture of rumen fluid containing a 60:40 ratio of forage to concentrate. For amplification of the prokaryotes (bacteria and archaea) in region V4, 16s rRNA primer 5’GTGCCAGCMGCCGCGTAA, GGACTACHVGGGTWTCTAAT3’ was employed. The data for rumen microbial abundance were analysed descriptively, while the data for rumen microbial diversity were obtained from the report on the Next Generation Sequencing Method. The microbial composition of each sample was tested for operational taxonomic units (OTUs) with a 97% identity rate on a valid label. The 16S rRNA gene sequencing yielded a total of 3,977 OTUs. Adding galangal and cineole EOs resulted in the same variation of the Shannon index. The population index (chao1 index) was highest when 60 µL of galangal EO was added, compared to 30 and 120 µL of galangal EO and cineole. In addition, providing 60 µL of galangal EO decreased the abundance of Prevotella ruminicola compared to the control and cineole doses. The addition of galangal EO also led to a decline in the number of Methanobacteriales. The population of the fibre‐degrading bacteria group (Ruminococcus albus and Ruminococcus flavefaciens) was higher in a dose of galangal EO than the control and cineole. Therefore, it can be concluded that the effective dose of galangal EO, i.e. 60 µL/300 mg (DM feed) in vitro, can reduce the abundance of Prevotella bacteria and methanogens.